The Role of Strategic Sourcing on the Performance of Large Manufacturing Firms in Kenya - Esther Njeri Muiruri; Noor Ismael Shale; Anthony Osoro (CV. Doki Course and Training, 2025)
Strategic sourcing is a critical supply chain driver that goes beyond the normal acquisition of goods, services, and materials, to encompass on the overall long-term business objective by optimizing value through cost, quality, efficiency, and supplier relationships. On the other hand, among the major attributes blamed to highly contribute to the stagnation and declining performance of Kenya’s manufacturing sector include high cost of production, poor quality products, and inefficiencies due to delays in production process. While strategic sourcing has been empirically proven to help in addressing these issues, its effective integration and embrace in Kenya’s manufacturing sector remains vague. This paper therefore sought to address the extent to which large manufacturing firms in Kenya have embraced strategic sourcing and whether its level of integration is correlated with the current performance status of the sector. A cross-sectional research design was used which informed a mixed method approach where both quantitative and qualitative methods were used. The study targeted 553 large manufacturing firms in Kenya, where heads of supply chain were the unit of observation. Using slovin sampling formula, a preferred sample size of 233 respondents was established where the respondents were selected using a stratified random sampling technique. A questionnaire with both closed-ended and open-ended questions was used to collect primary data, which was analyzed both quantitatively and qualitatively. The findings revealed that most of the large manufacturing firms in Kenya though recognized the essence of strategic sourcing, had ineffectively embraced it, and only relied on traditional reactive sourcing that mainly focuses on costs. It was revealed that strategic sourcing had a significant and positive (β = 0.823; P=0.000<0.05) impact on performance of large manufacturing firms in Kenya. The study concluded that the low embrace of strategic sourcing was significantly associated with the declining performance of the large manufacturing firms in Kenya. It was therefore recommended that the large manufacturing firms in Kenya through supply chain managers should go beyond the normal sourcing that primarily focuses on costs, to be more proactive and focus on value optimization in order to be competitive.